Efficient Perovskite Solar Cells by Reducing Interface‐Mediated Recombination: a Bulky Amine Approach. Issue 14 (21st February 2020) - Liang, Lusheng; Luo, Haitian; Hu, Junjie; Li, Hui; Gao, Peng
Abstract: The presence of non‐radiative recombination at the perovskite surface/interface limits the overall efficiency of perovskite solar cells (PSCs). Surface passivation has been demonstrated as an efficient strategy to suppress such recombination in Si cells. Here, 1‐naphthylmethylamine iodide (NMAI) is judiciously selected to passivate the surface of the perovskite film. In contrast to the popular phenylethylammonium iodide, NMAI post‐treatment primarily leaves NMAI salt on the surface of the perovskite film. The formed NMAI layer not only efficiently decreases the defect‐assisted recombination for chemical passivation, but also retards the charge accumulation of energy level mis‐alignment for vacuum level bending and prevents minority carrier recombination due to the charge‐blocking effect. Consequently, planar PSCs with high efficiency of 21.04% and improved long‐term stability (98.9% of the initial efficiency after 3240 h) are obtained. Moreover, open‐circuit voltage as high as 1.20 V is achieved at the absorption threshold of 1.61 eV, which is among the highest reported values in planar PSCs. This work provides new insights into the passivation mechanisms of organic ammonium salts and suggests future guidelines for developing improved passivation layers. Abstract : A unique ammonium salt, 1‐naphthylmethylamine iodide (NMAI) is shown to passivate the surface defects of perovskite, induce upward energy level bending and block electrons at the interface between the perovskite and hole transport layer in perovskite solar cells. These combined effects result in reduced non‐radiative recombination. Hence, more intensified electroluminescence and a champion open‐circuit voltage of 1.20 V are achieved in NMAI‐based devices.